Leısure tıme management ın marmara unıversıty and kilis 7 aralık unıversıty students traınıng ın sports scıences - Aytekin Alpullu; Ahmet Yılgın (Türk Spor ve Egzersiz Dergisi)
This sport science research in an undergraduate Faculty of Marmara University Sports Science and Kilis 7 Aralık University of Physical Education and Sports School students of “Leisure Management” ideas are evaluated.Free time management scale; Wei-Ching Wang et al. (2011) and Akgül and Karaküçük (2015) by adapting to Turkish by making validity and reliability study consists of 15 items and 4 sub-dimensions. 285 students from Marmara University Faculty of Sport Sciences and Kilis 7 Aralık University School of Physical Education and Sports participated in the study. In data analysis, descriptive statistics, t-test, ANOVA test were used. As a result of the statistical analysis, it was seen that the majority of the participants consisted of Marmara University students, while in the departments, there was a larger number of male students. In the other findings, it was understood that there was more participation in the 18-20 age group, they were single in marital status and they were more in the 1st class and they participated in their activities in leisure time 2-3 days a week. While there was a significant difference between the total scale scores of the participants and the variables of the universities, it was found that there was no significant difference in gender, marital status variables. There was a significant difference between the scale sub-dimensions and the activities of universities, age, leisure time and classes. As a result, it is understood that leisure time is better managed in metropolitan cities and that students who are studying in the field of sports should be directed to leisure time activities.